2016
DOI: 10.2147/hmer.s50172
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C in the Russian Federation: challenges and future directions

Abstract: Hepatitis C virus (HCV) infection is one of the most prevalent health problems in the world. Official registration of HCV infections in the Russian Federation started in 1994. Two clinical forms of infection – acute and chronic hepatitis C – are registered separately. Moreover, the HCV national surveillance system also includes reports from laboratories on results from testing ∼20 population risk groups for antibodies to HCV; approximately 15–16 million tests are performed annually. Modern epidemiological feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…A recent study of HCV prevalence in eight Russian cities reported that PWID in St. Petersburg had the highest prevalence of HCV (90 %) [ 10 ]. Recent estimates of HCV prevalence in Russia suggest that 3–4 % of the population is infected [ 1 , 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of HCV prevalence in eight Russian cities reported that PWID in St. Petersburg had the highest prevalence of HCV (90 %) [ 10 ]. Recent estimates of HCV prevalence in Russia suggest that 3–4 % of the population is infected [ 1 , 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Input assumptions are shown in Tables 1 and 2. Hepatitis C seroprevalence, viremic rate, and prevalence rate of acute infection was estimated based on epidemiological studies from Russia [3, 17, 24, 25]. Viremic rate refers to the proportion of chronic infected individuals out of all seropositive cases.…”
Section: Methodsmentioning
confidence: 99%
“…Since a loss to follow-up occurs at each step of the process, the need to consolidate the screening cascade has become apparent [11, 19, 21]. Suggested simplified algorithms, and even a one-step diagnostic procedure, have been proposed [17, 22], but in most instances a sound health economic evaluation is lacking, since studies are usually focused on direct costs only [15, 18]. The objective of this study was therefore to evaluate the cost-effectiveness of different screening algorithms for identifying patients with active hepatitis C infections while considering implications on the screening cascade in Russia.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of the epidemic process was assessed by the annual dynamics of the cumulative incidence of hepatitis B and C. (8)(9)(10) Results and Discussion Table 1 shows the average incidence rate for AHB in Almaty's adult population at 4-year intervals for 2003-2014: the AHB incidence by city areas steadily decreased by 3 or more times. These data conclusively demonstrate the epidemiological effectiveness of HBV vaccination.…”
Section: Methodsmentioning
confidence: 99%